Mitigation of DDoS attack instigated by compromised switches on SDN controller by analyzing the flow rule request traffic - R, Sanjeetha; Srivastava, Shikhar; Pokharna, Rishab; Shafiq, Syed; Anita Kanavalli, Dr (International Journal of Engineering and Technology, 2018)
Software Defined Network (SDN) is a new network architecture which separates the data plane from the control plane. The SDN controller implements the control plane and switches implement the data plane. Many papers discuss about DDoS attacks on primary servers present in SDN and how they can be mitigated with the help of controller. In our paper we show how DDoS attack can be instigated on the SDN controller by manipulating the flow table entries of switches, such that they send continuous requests to the controller and exhaust its resources. This is a new, but one of the possible way in which a DDoS attack can be performed on controller. We show the vulnerability of SDN for this kind of attack. We further propose a solution for mitigating it, by running a DDoS Detection module which uses variation of flow entry request traffic from all switches in the network to identify compromised switches and blocks them completely.